2021
DOI: 10.3389/fcvm.2021.721393
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-Induced Blood Pressure Reduction: Mechanisms for the Treatment of Hypertension via the Gut

Abstract: Hypertension is a major risk factor for the development of cardiovascular disease. As more research into the gut microbiome emerges, we are finding increasing evidence to support that these microbes may have significant positive and negative effects on blood pressure and associated disorders. The bacterial-derived metabolites that are produced in the gut are capable of widespread effects to several tissue types and organs in the body. It is clear that the extensive metabolic function that is lost with gut dysb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 130 publications
(103 reference statements)
0
16
0
2
Order By: Relevance
“…Although the underlying mechanisms by which Limosilactobacillus fermentum reduced blood pressure have not been assessed in the present study, some possible pathways related to probiotic-induced-hypotensive effects have been proposed. 33 First, it has been demonstrated that gut barrier integrity can be rescued by probiotic therapy, reducing LPS-translocation, inflammation, sympathetic activity, endothelial dysfunction, and blood pressure. 29,34 Second, short-chain fatty acids (SCFA), including acetate, propionate, and butyrate, are produced by specific gut microbes and can be enhanced during probiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms by which Limosilactobacillus fermentum reduced blood pressure have not been assessed in the present study, some possible pathways related to probiotic-induced-hypotensive effects have been proposed. 33 First, it has been demonstrated that gut barrier integrity can be rescued by probiotic therapy, reducing LPS-translocation, inflammation, sympathetic activity, endothelial dysfunction, and blood pressure. 29,34 Second, short-chain fatty acids (SCFA), including acetate, propionate, and butyrate, are produced by specific gut microbes and can be enhanced during probiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiome has various effects for host homeostasis contributing to blood pressure regulation [43]. For example, changes in gut microbiome in SHR reduced blood pressure through the reduction of SNA [44].…”
Section: Discussionmentioning
confidence: 99%
“…Indoles are aromatic, heterocyclic, organic compounds that can be produced through gut microbiota. Gut microbes can express indole‐3‐glycerol phosphate synthase, indole‐3‐glucerol phosphate lyase, and indole synthase, which may promote the production of indole 106 . Indole has been reported to be associated with hypertension.…”
Section: The Potential Mechanisms Involved In the Regulation Between ...mentioning
confidence: 99%
“…Gut microbes can express indole-3-glycerol phosphate synthase, indole-3-glucerol phosphate lyase, and indole synthase, which may promote the production of indole. 106 Indole has been reported to be associated with hypertension. Administration of indole increased BP dose-dependently in rats.…”
Section: Immunity Responsementioning
confidence: 99%